A translanguagepedagogy to promote Biotechnology concept engagement and academic literacy in a linguistically-diverse university context - Nakhooda, Muhammad; Paxton, Moragh (Critical Studies in Teaching and Learning, 2023)
Following the call for transformation, higher education institutions in South Africa were required to promote and implement indigenous languages in teaching and learning. This has led to various strategies and resources being explored and implemented, multilingual glossaries among them. In science, where English remains the global means of communication, our experience has been that such interventions are often underutilized. A more inclusive, holistic pedagogy is required to adequately prepare students, especially non-English speakers, for international scientific engagement. One such pedagogy is presently proposed and tested. Its purpose is to harness the dominant language - that which is most active in the learners’ minds - to first promote epistemological access to difficult scientific concepts, and after concept acquisition, develop the required English, scientific, and academic literacy. Biotechnology undergraduate students at Cape Peninsula University of Technology (CPUT) - many of whom are international - reported enhancing their learning experience and recognised the significance of their dominant language in deep learning as a result of this translanguage pedagogy. Such a pedagogy demonstrates that multilingualism, far from being viewed as an impediment to teaching and learning, should be seen as a rich resource that needs to be harnessed to facilitate epistemic access, cognitive development, transformation, social cohesion, and respect for all languages.